Birt-Hogg-Dubé Syndrome and Hereditary Leiomyomatosis and Renal Cell Carcinoma Syndrome: An Effective Multidisciplinary Approach to Hereditary Renal Cancer Predisposing Syndromes - Al-Shinnag, Mohammad; Marfan, Helen; Susman, Rachel; Wakeling, Jan; Gustafson, Sonja; Wood, Simon; Mallett, Andrew John (Frontiers in Oncology, 2021)
Aim We aimed to describe and analyse clinical features, characteristics, and adherence to surveillance guidelines in an Australian Birt-Hogg-Dubé Syndrome (BHD) and Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC) cohort. Methods All identified patients with a diagnosis of BHD or HLRCC at RBWH 01/01/2014-01/09/2019 were included (HREC/17/QRBW/276). All patients were initially assessed and counselled by a Clinical Geneticist and then referred to an Adult Nephrologist. Baseline and incidental clinical variables were extracted and analysed. Results 57 patients were identified (28 BHD, 29 HLRCC) with a median age of 47 years. The median and cumulative follow up were 1 year and 99 years respectively. Baseline renal MRI occurred in 40/57 patients and 33/57 had regular MRI as per the national guidelines (eviQ). Of 18/57 without baseline imaging 9 were yet to have imaging, 7 were lost follow up and 2 patients had logistic difficulties. RCC was diagnosed in 11/57 patients: 2/28 with BHD were diagnosed with RCC aged 73 and 77 both prior to commencement of surveillance. 9/29 patients with HLRCC were diagnosed with RCC (1/29 during surveillance at 47 years of age) and 8/29 prior to commencement of surveillance (11-55 years). Amongst BHD patients, cutaneous fibrofolliculomas were noted in 15 patients, lung cysts were detected in 7 patients, spontaneous pneumothoraces in 5 patients, and parotid oncocytoma in 2/28. Amongst those with HLRCC, cutaneous leiomyomas were noted in 19/29, cutaneous leiomyosarcoma diagnosed in 1/29 and uterine fibroids in 13 female patients. Conclusion Evidence-based RCC screening in BHD and HLRCC cohort is feasible and able to identify incidental renal lesions. Multidisciplinary patient management enables expedited genetic counselling, diagnosis, longitudinal screening and RCC management. The success of this clinical model warrants consideration of undertaking longitudinal screening of BHD and HLRCC patients by nephrologists.